Analysis of Regional Development and The Needs of Clean Water Services in Medan City - Milanie, Feby; ., Sumono; ., Rujiman (Journal of Economics and Behavioral Studies, 2014)
This study aims to analyze the influence of biophysical, economic, location, socio-cultural, institutional and environmental aspects on the water supply and the need for clean water in Medan city. Clean water was originally consideredas social goods that were freely accessed. The need for clean water for the population in Medan city is heightened due to the population growth, the increase on economic activities such as industrial growth in small-scale, medium and large industries, the development of public facilities and the increasing welfare of the community. The primary and secondary data obtained from relevant agencies and public in Medan city are used in this study. The secondary data were obtained starting in 1990 - 2012, while primary data were obtained from 30 respondents. The analysis model used is the structural equation models. The results have shown that; (i) biophysical, economic, location, sociocultural, institutional, environmental aspects positively influence the water supply and the need for clean water; (ii) there is a greater influence of water needs on the water supply, as compared to the effect of water supply to the needs of clean water.